LEGAL EDUCATION OF SCHOOLCHILDREN IN PHYSICAL CULTURE LESSONS - Ghantarchyan, Evelina (Գիտությունը սպորտում. արդի հիմնախնդիրներ, 2021)
High level of legal culture is a key component for sophisticated development of a person. Legal education of schoolchildren strengthens their position in life, increases their civic engagement. The physical education process of schoolchildren, consistent with complex physical development, adequate physical preparedness and ensuring the development of special knowledge, creates quite favorable conditions for the legal education of pupils. The survey results indicated that schoolchildren have poor understanding of the role and importance of physical culture in the midst of multifaceted personality development. They do not consider the process of physical education as a tool of moral, intellectual, aesthetic, ideological and legal education.